2020
DOI: 10.1101/2020.06.15.152488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elongation Inhibitors do not Prevent the Release of Puromycylated Nascent Polypeptide Chains from Ribosomes

Abstract: Puromycin is an amino-acyl transfer RNA analog widely employed in studies of protein synthesis. Since puromycin is covalently incorporated into nascent polypeptide chains, anti-puromycin immunofluorescence enables visualization of nascent protein synthesis. A common assumption in studies of local messenger RNA translation is that the anti-puromycin staining of puromycylated nascent polypeptides in fixed cells accurately reports on their original site of translation, particularly when ribosomes are stalled with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
5
1
Order By: Relevance
“…We treated animals/cells with CHX/PMY, isolated ribosomes from cell lysates on sucrose gradients in monosome and polysome fractions, blotted fractions onto nitrocellulose and stained with antibodies against RPL7 or PMY. The robust PMY signal shows that, contrary to recent claims 38,39 , PMY does not completely release nascent chains when ribosomes are previously exposed to CHX (Figure 5A).…”
Section: Contribution Of Monosomes Vs Polysomes To T Cell Translationcontrasting
confidence: 76%
“…We treated animals/cells with CHX/PMY, isolated ribosomes from cell lysates on sucrose gradients in monosome and polysome fractions, blotted fractions onto nitrocellulose and stained with antibodies against RPL7 or PMY. The robust PMY signal shows that, contrary to recent claims 38,39 , PMY does not completely release nascent chains when ribosomes are previously exposed to CHX (Figure 5A).…”
Section: Contribution Of Monosomes Vs Polysomes To T Cell Translationcontrasting
confidence: 76%
“…Recent studies showed that puromycylated peptides are released and diffuse quickly from the site of translation in cultured cell lines, leading to inaccuracy in identification of translation sites (Enam et al, 2020;Hobson et al, 2020) . It is likely that the dense environment of the myofiber restricts diffusion of labeled peptides away from the site of synthesis (Papadopoulos et al, 2000) , avoiding the pitfalls of this technique observed in dividing cells.…”
Section: Spatially Dispersed Translation In the Cytoplasm Requires Intact Microtubulesmentioning
confidence: 99%
“…Treating the cells with puromycin in a com bination with cycloheximide leads to the accumulation of ribosomes exclusively on start codons, which facilitates their identification by ribosome profiling [127]. On the other hand, the combined effect of puromycin and other antibiotics depends on the ratio and concentrations of these compounds and cannot always be predicted, which may lead to artifacts [128,129]. The activity of puromycin is unique; for example, structurally similar antibiotic A201A (see above) does not act as a peptide bond accep tor and only inhibits the peptidyl transferase reac tion [13,40].…”
Section: Inhibitors Of Eukaryotic Ribosomementioning
confidence: 99%